Candidaturas coletivas no Brasil : encontros e desencontros entre movimentos sociais e partidos políticos nas eleições legislativas de 2022 - Cláudia Torres Lopes (2024)
This dissertation aims to analyze collective candidacies in the context of the 2022 legislative elections, focusing on the interaction between social movements and political parties. Using the electoral arena as the locus of analysis, an institutional space typically linked to parties and contested by movements, we seek to conduct a relational analysis to envision the expression of the interdependencies and mutual constitution involved. Arguing that collective candidacies bring inventiveness to this interaction and reflect complex configurations, we hypothesize three patterns associated with the meetings and mismatches between movements and parties: i) cooperative: the relationship between both tends to be more fluid or even collaborative; ii) pragmatic: allows movements to promote their projects within the political system and parties to access their political capital; and iii) historical: the longevity and solidity of bonds favor the reception and maintenance of collective candidacies within a party organization.To support this argument and operationalize the hypotheses, we adopted a multimethod approach. We mapped and analyzed the profile of collective candidacies based on primary data provided by the Superior Electoral Court, using a set of sociodemographic and party variables. To advance in identifying the themes and causes advocated, as well as the social movements or other organizations and associative modalities, we resorted to quantitative content analysis of images published on Instagram. Additionally, we conducted case studies of four collective candidacies for state legislative office launched by the Partido Socialismo e Liberdade (PSOL) through in-depth interviews with nine co-candidates. Supporting the concept that these types of candidacies aim to broaden the representation of bodies and agendas in institutional politics through creative and contingent adaptations alongside social movements and political parties, we outlined three main conclusions. The first concerns the profile of collective candidacies. We observed the diversification of the parliamentary candidacy framework and the democratization of political representation, particularly regarding the entry of black women into the electoral arena. Among the co-candidates, we recognized a set of overlapping associative bonds, encompassing different spheres of action and political influence, which are sometimes interconnected, forming a network. We also noted the increased involvement of these types of candidacies with social issues, such as health, environment, education, and culture. The second conclusion is that there is a long-standing cooperation between the co-candidates and the state in its various institutions, a relationship that has even guided the dynamics and strategies experienced within the party. Finally, the third conclusion is that there are several possibilities in the interaction between social movements and political parties, taking the form of a continuum of alignment and influence between them that can move continuously within this spectrum as political and institutional circumstances change. These findings introduce new explanatory resources that enrich traditional theoretical models on the relationships between social movements and parties and, mainly, highlight vulnerable or underdeveloped points in the recent literature on collective candidacies that may be useful to inspire further analyses.